Independence for Internal Auditors: Is it Necessary? - Nanang Setiawan; Riskiyatur Rohemah; Ismi Fitri Aulia (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2023)
Independence is needed to maintain the quality of audit results and the credibility of financial reports, especially for external auditors independent of clients. As for the internal auditors within the organization, is independence still necessary? This article is intended to analyze the independence aspects of internal auditors and how internal auditors, in their assignments, maintain and ensure the quality of audit results that are credible. This study uses a descriptive qualitative method with a literature study approach. The results of the analysis show that internal auditors who are in the organizational structure of an entity still require independence in their assignments, even though they are under management (directors or commissioners), but in carrying out their duties they must remain independent of the department being audited so that during the audit process and reporting they remain objective, neutral, and impartial. An accurate audit report is addressed to management to evaluate performance and follow up on improvements in the department being audited. This study tries to fill the gap in research on audit independence among internal auditors because almost all research on audit independence involves external auditors. This study contributes to increasing audit independence literacy for internal auditors and has implications for the need for an independence code of ethics for internal auditors